Mechanical performance of natural fiber-reinforced composites for the strengthening of masonry. (August 2015) - Codispoti, Rosamaria; Oliveira, Daniel V.; Olivito, Renato S.; Lourenço, Paulo B.; Fangueiro, Raul
Abstract: The growing concerns regarding the environmental impact generated by the use of inorganic materials in different fields of application increased the interest towards products based on materials with low environmental impact. In recent years, researchers have turned their attention towards the development of materials obtained from renewable sources, easily recoverable or biodegradable at the end of use. In the field of civil structures, a few attempts have been done to replace the most common composites (e.g. carbon and glass fibers) by materials less harmful to the environment, as natural fibers. This work presents a comprehensive experimental research on the mechanical performance of natural fibers for the strengthening of masonry constructions. Flax, hemp, jute, sisal and coir fibers have been investigated both from physical and mechanical points of view. The fibers with better performance were tested together with three different matrices (two of organic nature) in order to produce composites. These experimental results represent a useful database for understanding the potentialities of natural fibers as strengthening systems.